Cost-effective high-gain DC-DC converter for elevator drives using photovoltaic power and switched reluctance motors - Baskaran, J.; Naghapushanam, Manimaran; Ganapathy, Mahalakshmi; Meena, P.; Meena, V. P.; Azar, Ahmad Taher; Hameed, Ibrahim A. (Frontiers in Energy Research, 2024)
Low-cost photovoltaic-powered elevators (PVPEs) have gained ever-increasing attention in the last few years for their advantages in terms of renewable energy and low maintenance costs after installation. In this paper, four high-step-up DC-DC converters for low-voltage sources such as solar photovoltaic, fuel cells, and battery banks are proposed. Their performances are evaluated in terms of optimal capability and high reliability. Among the four proposed architectures, the bootstrap converter is selected for its ability to restrict losses and other redundant parameters. The proposed converter drives the inverter-driven switched reluctance motor (SRM) assembly through a directly coupled method, which eliminates the need for battery banks while aiding in cost reduction. The prototype model is implemented, and results are validated, showing promising performance and thus being very efficacious for application to low-cost PVPEs.